2013
DOI: 10.1080/15389588.2013.803279
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations and Fatalities in Crashes With Light Trucks

Abstract: Though previous studies have shown high fatality costs associated with light trucks, this study is the first to explore the hospitalization costs associated with these vehicles. The existing traffic liability systems (tort or no-fault systems) likely fail to fully make light trucks accountable for costs they impose on other cars, pedestrians, and other road occupants. Our findings suggest the importance of a close examination of a broad range of cost implications even beyond hospitalization and fatality costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition, the extra sturdiness and safety equipment present in luxury cars may reduce the bodily injury of their drivers and passengers. On the other hand, bodily injury may increase as luxury car ratio increases if the luxury cars' sturdiness or safety features cause more severe bodily injury of others on roads, as is sometimes the case with accidents involving SUVs and pickup trucks (Meyer and Gomez-Ibanez, 1981;White, 2004;Wenzel and Ross, 2005;Anderson, 2008;Karaca-Mandic and Lee, 2014). If luxury cars reduce bodily injury losses, this effect may offset the increased cost from the physical damage liability.…”
Section: Other Discussion Luxury Cars and Bodily Injury Liabilitymentioning
confidence: 99%
“…In addition, the extra sturdiness and safety equipment present in luxury cars may reduce the bodily injury of their drivers and passengers. On the other hand, bodily injury may increase as luxury car ratio increases if the luxury cars' sturdiness or safety features cause more severe bodily injury of others on roads, as is sometimes the case with accidents involving SUVs and pickup trucks (Meyer and Gomez-Ibanez, 1981;White, 2004;Wenzel and Ross, 2005;Anderson, 2008;Karaca-Mandic and Lee, 2014). If luxury cars reduce bodily injury losses, this effect may offset the increased cost from the physical damage liability.…”
Section: Other Discussion Luxury Cars and Bodily Injury Liabilitymentioning
confidence: 99%
“…Some studies have shown an association between these two phenomena, including an American cross sectional study from 2002 [4], a retrospective analysis focused on New York City in the 1990s [5], and an Australian study summarizing low speed fatalities on young children in the late 1990s [6]. The increased morbidity and mortality that light trucks impose on vulnerable road users are likely due to light trucks' large size, taller body, stiffer front structure, and decreased visibility for their drivers [7]. Americans walk and bike less than many of their rst world counterparts [8], however this varies by state [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown an association between these two phenomena, including an American cross sectional study from 2002 (Paulozzi 2005 ), a retrospective analysis focused on New York City in the 1990s (DiMaggio et al 2006 ), and an Australian study summarizing low speed fatalities on young children in the late 1990s (Neeman et al 2002 ). The increased morbidity and mortality that light trucks impose on vulnerable road users are likely due to light trucks’ large size, taller body, stiffer front structure, and decreased visibility for their drivers (Karaca-Mandic and Lee 2014 ).…”
Section: Introductionmentioning
confidence: 99%